BENTUK PENYAJIAN TARI RATIB SAMAN DALAM TEPUNG TAWAR DI DUSUN SEBADI KABUPATEN SAMBAS - Fitrina, Yola; Ismunandar, Ismunandar; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is to find out the basis and support that can be found in Ratib Saman's dance in the Fresh Flour Ceremony. The results of this study are a description of the main elements and supporting elements of Ratib Saman dance in the Fresh Flour Ceremony. There are thirteen kinds of motion which are divided into four parts, namely the opening variety, the core variety, the variety of connectors and the variety of covers. The floor design used has a pattern of vertical, horizontal lines, and V. Ratib Saman's dance is an offering dance to God to ask for protection after moving to a new house. The dancer's movements adjust to the tempo of the music. The music uses Tar, long drum, kabasa, tambourine and tambourine. The makeup and custom used are Malayu custom Sambas bay belangak using kain lunggi or cual cloth and also uses black skullcap, makeup that is used naturally or without make up. The venue used is on the home page, inside the house and also on the show stage. The results of this study will be implemented in high school (SMA) in learning arts and culture and become learning theory consisting of Core Competencies 1 to.Keywords: form of dance presentation, Ratib Saman dance, tepung tawar ceremony, Teluk Keramat